2016
DOI: 10.1111/apt.13731
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of faecal calprotectin in patients with inactive inflammatory bowel disease

Abstract: SUMMARY BackgroundFaecal calprotectin, an established biomarker used to assess mucosal inflammation, has been shown to correlate with endoscopic activity in inflammatory bowel disease (IBD). Longitudinal monitoring of faecal calprotectin, however, has rarely been employed beyond assessment of therapy response and post hoc analyses of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 35 publications
6
48
1
1
Order By: Relevance
“…The association in this study may be related to the higher rate of anti‐TNF α agent use, hence a greater potency of suppressing inflammation, in patients with Crohn's disease compared to ulcerative colitis (Crohn's disease 40% vs. ulcerative colitis 7%, P < 0.001). We however did not find an association between use of anti‐TNF α agents and the risk of symptomatic relapse, nor did the lone previous study which also reported the effect of anti‐TNF α on symptomatic relapse in adults with IBD in clinical remission . Nevertheless, the number of anti‐TNF α users that subsequently relapsed, in our cohort and the latter study, were low, which may have impeded determination of an accurate association.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The association in this study may be related to the higher rate of anti‐TNF α agent use, hence a greater potency of suppressing inflammation, in patients with Crohn's disease compared to ulcerative colitis (Crohn's disease 40% vs. ulcerative colitis 7%, P < 0.001). We however did not find an association between use of anti‐TNF α agents and the risk of symptomatic relapse, nor did the lone previous study which also reported the effect of anti‐TNF α on symptomatic relapse in adults with IBD in clinical remission . Nevertheless, the number of anti‐TNF α users that subsequently relapsed, in our cohort and the latter study, were low, which may have impeded determination of an accurate association.…”
Section: Discussioncontrasting
confidence: 92%
“…Faecal calprotectin level has already been shown to be predictive of symptomatic relapse in adult patients with IBD . Similar to our results, the majority of studies in adults found a higher FC level in patients who developed a relapse compared with those who remained in clinical remission .…”
Section: Discussionsupporting
confidence: 91%
“…FC has been shown to be a reliable marker for assessing IBD disease activity [24] and in predicting mucosal healing and risk of relapse in CD patients [25][26][27]. CRP was also found to be a predictor of surgery in subgroups of patients with either UC or CD [28].…”
Section: Treatment Goals and Therapeutic Approaches -Differences Withmentioning
confidence: 99%
“…With regard to the role of fCP in predicting response to thiopurine therapy, there are to our knowledge to date no published studies that interpret its predictive utility. The detailed role of fCP in IBD along with its ability to predict response to other forms of treatment than thiopurines alone are described in a number of up to date reviews (11,12,63,(80)(81)(82)(83)(84).…”
Section: Fecal Biomarkersmentioning
confidence: 99%